Pretreatment Techniques for Drug Residues in the Environment before their Quantitation - Tang, Jingyi; Yang, Min; Yao, Shun (Current Analytical Chemistry, 2021)
Background: More and more chemical substances are being released to the environment. Therefore, environmental problems caused by different pollutants have attracted long-term attention. Objective: Sample pretreatment has always been the bottleneck restricting the development of residual drug analysis, so the latest development in various pretreatment technologies and current status for different residual drugs in environmental samples are reviewed. Methods: For systematic and explicit descriptions, all of the contents were elucidated and summarized in a series of independent parts. In each part, it started from the research background or a conceptual framework and then specific examples were introduced to illustrate the theme. Finally, the important conclusions were drawn and its future was out looked after the discussion about related key problems appearing in each mentioned research. Results: The whole review was composed of four parts, and 111 papers were cited in total. Six figures were used to depict progress in potential pretreatment technologies for residual drugs in the environment, and nine tables were employed to summarize pretreatment and analysis results for various residual drugs in the environment. Conclusion: This review placed emphasis on the development of pretreatment techniques of residual drugs in a specific manner, leading to meaningful and valuable related information to some related fields and thus promoting further research and application of related methods. The deep exploration for key scientific problems is the driving force to their effective detection and strict control.
Keywords: environment